Capitalism and Early Modernity in the Middle Ages: An Overview of Ideological Trends - Oleg V. Kim (СибСкрипт, 2025)
Capitalism first emerged in the Middle Ages against the backdrop of social and cultural innovations that may change the traditional concept of the Middle Ages as a period of pure feudalism. These innovations were global in nature and reflected the mutual influence of Western and Eastern civilizations. They also manifested a certain continuity with Classical European culture and society. The article introduces the term of Early Modernity to describe these phenomena and trends. The historiographic analysis focused on foreign and domestic studies published in 1970–2024. The ideas, institutions, and practices of early modernity found their reflection in the theories of transitional society, modernization, and proto-industrialization, as well as in the studies that covered the trade revolution of XII–XIII centuries. The new temporality and space arrangement of the global Middle Ages appeared in the images of a single Afro-Eurasia and the Post-Classical Period. As the status of medieval technologies, knowledge systems, and ideas about the world increased, it yielded the concept of global technological and cultural rise in the XI–XIII centuries. Such expanded interpretation of the Middle Ages and genesis of capitalism caused a critical reaction from medievalists. While acknowledging the shortcomings of the standard approach to Western European feudalism, they stick to the key criteria in defining the classical Middle Ages and the feudal revolution. However, macrohistorical studies seriously consider the world-system perspective and the context of global history.